A Deconstruction Lattice Description of the D1/D5 Brane World-Volume Gauge Theory - Joel Giedt (Advances in High Energy Physics)
I generalize the deconstruction lattice formulation of Endres and Kaplan to two-dimensional super-QCD with eight supercharges, denoted by (4,4), and bifundamental matter. I specialize to a particularly interesting (4,4) gauge theory, with gauge group U (